Determinação do máximo déficit acumulado de oxigênio de nadadores por meio da técnica de retro extrapolação - Campos, Eduardo Zapaterra [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Due to the need to optmize the methods of anaerobic capacity determination, the aim of the present doctor thesis was validate the evaluation of accumulated oxygen deficit (AOD) by the backward extrapolation technique (AODRED). For this, 25 swimmers were evaluated and four scientific works were developed. The first study aimed to compare VO2Peak and sVO2Peak of swimmers obtained after a maximal 400 m effort and free-swimming incremental test. Eleven swimmers performed a maximal 400m effort and an incremental protocol to determine both variables. Besides no difference between VO2Peak (3.86 ± 0.85 L∙min-1 vs. 4.09 ± 0.93 L∙min-1), the sVO2Peak 1.39 ± 0.12 m∙s-1 vs. 1.34 ± 0.13 m∙s-1) was higher in the incremental test. The second study aumed compare AODRED (i.e. sum of lactic and alactic metabolism) with the AOD after a maximal 400m effort. The AOD was considered as the difference between theoretical demand (TD) and aerobic contribution (Aer), while AODRED was evaluated by the sum of anaerobic metabolisms. No difference between AOD (3.29 ± 1.34 LO2) and AODRED (3.24 ± 1.56 L O2), significant correlation (r = 0.95), and low mean standard estimative error (0.04 L) were found between the methodologies. Since no difference was found, the third study aimed to verify the possibility to estimate Aer only by the use of AODRED. Six swimmers were submitted to a maximal 400m effort with snorkel. The Aer estimated by the rectangular demand (i.e. VO2Peak·effort time; AerRD) was not different from Aer (10.36 ± 1.56 L vs. 10.31 ± 1.48 L), and presented low mean error (-0.15 L). Thus, since AODRED is determined by peak lactate concentration and off transient oxygen kinetics, it would be possible the AODRED by the backward extrapolation technique. Thus, the forth study aimed to test the reliability and validity of free-swimming AODRED (i.e. backward extrapolation). For this, eight swimmers performed two 400m efforts without snorkel ...

Devido à necessidade de otimização dos métodos de determinação da capacidade anaeróbia, o objetivo da presente tese de doutorado foi validar a avaliação do déficit acumulado de oxigênio (AOD) por meio da técnica de retro extrapolação (AODRED). Para isso, 25 nadadores foram avaliados e quatro trabalhos foram desenvolvidos. O primeiro trabalho objetivou comparar o VO2Pico e a vVO2Pico de nadadores obtidos após esforço máximo de 400 m e teste incremental em nado livre. Onze nadadores realizaram esforço máximo de 400m e protocolo incremental para determinar ambas variáveis. Apesar de nenhuma diferença entre VO2Pico (3.86 ± 0.85 L∙min-1 vs. 4.09 ± 0.93 L∙min-1), a vVO2Pico (1.39 ± 0.12 m∙s-1 vs. 1.34 ± 0.13 m∙s-1) foi superior durante teste incremental. O segundo trabalho objetivou comparar o AODRED (i.e. soma dos metabolismos lático e alático) com o AOD após esforço máximo de 400m. Para isso seis atletas foram submetidos à quatro exercícios submáximos e um esforço máximo de 400m. O AOD foi considerado a diferença entre a demanda teórica (DT) e a contribuição aeróbia (Aer), enquanto o AODRED foi avaliado pela soma dos metabolismos anaeróbios. Nenhuma diferença entre AOD (3.29 ± 1.34 LO2) e AODRED (3.24 ± 1.56 L O2), correlações significantes (r = 0.95) e baixo erro médio de estimativa (0.04 L) foram encontrados entre as metodologias. Haja vista que nenhuma diferença foi encontrada, o terceiro estudo objetivou verificar a possibilidade de se estimar a Aer apenas pelo uso do AODRED. Seis nadadores foram submetidos à um esforço máximo de 400m com snórquel. A Aer estimada pela demanda retangular (i.e. VO2Pico·tempo de esforço; AerRD) não foi diferente da Aer (10.36 ± 1.56 L vs. 10.31 ± 1.48 L), além de apresentar baixo erro médio (-0.15 L). Dessa forma, como o AODRED é determinado pelas concentrações pico de lactato e cinética off do consumo de oxigênio, seria possível avaliar o...
Keywords: Swimming; Natação; Capacidade anaeróbica; Oxigênio - Transporte fisiológico